An experimental study on the post-cracking behaviour of Hybrid Industrial/Recycled Steel Fibre-Reinforced Concrete. (30th September 2015) - Martinelli, Enzo; Caggiano, Antonio; Xargay, Hernan
Highlights: Recycled Steel Fibres can be obtained from end-of-life tyres. They can partially-to-totally replace Industrial Steel Fibres. Fibre replacement aims at enhancing sustainability of cementitious composites. A decay in the post-cracking behaviour is expected in FRC with recycled fibres. This paper is intended at investigating and quantifying such a decay. Abstract: This paper investigates the mechanical behaviour of FRC made with both Industrial and Recycled Steel Fibres recovered from waste tyres. Specimens of various mixtures, characterised by the same volume fraction of fibres, but different proportions of industrial and recycled reinforcement were tested both in compression and bending. The results highlighted a fairly negligible influence of fibres in terms of compressive strength, whereas a significant decay in the post-cracking behaviour was observed in specimens with higher fractions of recycled fibres. However, a significant enhancement in the bending response was observed with respect to the case of plain concrete, even for specimens reinforced by recycled fibres only.